1836. Characteristics of Nursing Homes Associated With Self-reported Implementation of Centers for Disease Control and Prevention (CDC) Core Elements of Antibiotic Stewardship. (26th November 2018) - Thompson, Nicola D; Brown, Cedric; Eure, Taniece; Penna, Austin; Barney, Grant; Barter, Devra; Buhr, Nicolai; Clogher, Paula; Dumyati, Ghinwa; Epson, Erin; Frank, Linda; Godine, Deborah; et al.
Abstract: Background: CDC released the Core Elements of Antibiotic Stewardship (Core Elements) for Nursing Homes (NHs) in 2015. In 2017, CDCs Emerging Infections Program (EIP) evaluated uptake of the Core Elements in a cohort of NHs. Methods: NHs from California, Colorado, Connecticut, Georgia, Maryland, Minnesota, New Mexico, New York, Oregon, and Tennessee were randomly selected to participate in a CDC EIP antimicrobial use prevalence survey; participation was voluntary. A NH leader (typically Director of Nursing or Infection Preventionist) completed a CDC questionnaire to self-report facility implementation of 15 individual activities within the 7 domains of the Core Elements. The number and percentage of facilities reporting "Yes" to each activity and a facility stewardship score (range 0–15, 1 point per activity) were calculated. Associations between the stewardship score and facility-level factors, obtained from the questionnaire and publically available Centers for Medicare and Medicaid Services (CMS) NH quality data, were identified using Analysis of Variance (Proc GLM) in SAS 9.4; a P < 0.05 was considered significant. Results: In 161 NHs (mean certified beds 118, 92% dual certified, 68% for-profit), the % of NHs reporting implementation of the 15 activities (figure) ranged from 25% (has a formulary of antibiotic agents, providers required to perform an antibiotic "time-out") to 88% (providers required to document dose, duration and indication). The median facility stewardship score was 9 (interquartile range 7–12). A higher stewardship score was significantly associated with having: an infection preventionist who completed a certified training course (Yes vs. No, P = 0.029), higher number of attending physicians per 100 NH beds (upper quartile vs. lower three quartiles, P = 0.029), and higher CMS quality measure score (scale of 1 to 5 points, P = 0.025). Conclusion: These data, collected approximately 2 years after release of the Core Elements, show NHs have begun to implement many policies or practices consistent with CDC antibiotic stewardship guidance. However, improved understanding of the uptake and barriers associated with implementation of the Core Elements can inform development of stewardship initiatives, identify NHs in need of stewardship interventions, and accelerate adoption. Disclosures: All authors: No reported disclosures.